High prevalence of unstable antibiotic heteroresistance in cyanobacteria causes resistance underestimation. (1st September 2021) - Wang, Zhiyuan; Chen, Qiuwen; Zhang, Jianyun; Yan, Hanlu; Chen, Yuchen; Chen, Cheng; Chen, Xiaoxue
Highlights: Multiple antibiotic heteroresistance is widespread in cyanobacteria Heteroresistance is mostly unstable due to gene amplification and high fitness cost Unstable heteroresistance incurs cyanobacteria-derived resistance underestimation Antibiotic pressure promotes both polyclonal and monoclonal heteroresistance Abstract: Both cyanobacterial bloom and antibiotic resistance have aggravated worldwide and posed a global threat to public health in recent years. Cyanobacteria can exhibit discrepancy between their resistance genotype and susceptible phenotype due to antibiotic heteroresistance, which leads to difficulties in unambiguously classifying cyanobacterial strains as susceptible or resistant. Here we profiled the prevalence and mechanisms of antibiotic heteroresistance in cyanobacterial strains isolated from 50 sites across four eutrophicated lakes in China. Among 300 cyanobacterial isolates tested against 19 different antibiotics, over 90% of cyanobacterial isolates exhibited HR to multiple antibiotics and 19.5% of isolate/antibiotic interactions classified as susceptible by traditional minimum inhibitory concentration (MIC) estimates were designated heteroresistant. Over 97% of these monoclonal HR cases were unstable, with an increased resistance of subpopulations due to amplification of known resistance genes with high fitness cost. Wide-type cyanobacterial isolates of Synechococcus, Synechocystis, Anabaena and Microcystis aeruginosa exposed to sub-MIC level of four antibiotics evolved high-level resistance with little fitness cost, resulting in stable polyclonal HR. Both stable polyclonal HR and unstable monoclonal HR observed in different cyanobacterial strains can be promoted under environmental levels of antibiotic pressure. The highly prevalent and unstable monoclonal HR with the potential for susceptibility misclassification highlighted underestimation of cyanobacteria-derived antibiotic resistance. Cost-effective strategies should be developed to identify heteroresistance in cyanobacteria and to avoid false positive or negative results in traditional susceptibility testing. Graphical Abstract: Image, graphical abstract